Low Cost Bluetooth Controlled Fire Extinguisher Robot Using Light Intensity Sensor - SAI PAVAN KUMAR, RACHAPUDI S N V M K; NUTHALAPATI, Prof. SURESH (IJRDO - Journal of Electrical And Electronics Engineering, 2016)
The Project is designed to develop a Low Cost firefighting Robot using Bluetooth technology for remote operation. Bluetooth HC-05 module is used for this purpose. The robotic vehicle is loaded with water tanker and a pump which is controlled over wireless communication to sprinkle water. At the transmitting end using push Bluetooth app, commands are sent to the receiver to control the movement of the robot either to move forward, backward and left or right etc. At the receiving end three motors are interfaced to the microcontroller where two of them are used for the movement of the vehicle and the remaining one to sprinkle the water during the fire. A water tank along with water pump is mounted on the robot body and its operation is automatically detected by the photodiode based (Light Intensity) Fire detecting sensor, which is possible by LM393. The whole operation is controlled by an ATMEGA328 series microcontroller. A motor driver IC, L293D is interfaced to the microcontroller through which the controller drives the motors.